Employment in Facility Services: The EU and the US - Redlein, Alexander; Stopajnik, Eva (Journal of Applied Business and Economics, 2023)
There is a lack of reports on the Facility Services (FS) sector. This article tries to close that gap by analyzing and comparing employment in FS in the EU and the US. The analysis is based on European norms and the statistical classification systems in the EU (NACE) and the US (NAICS). Results show that in the EU in 2019, more than 14 million employees work in the FS sector. In the US, there are more than 9 million. In the EU, this is almost 11% of all employees in the business economy; in the US, this is more than 9%.